Potting substrate effect on yield and quality of strawberry (Fragaria × ananassa) in terrace gardening - KUMAR, PRADEEP; KUMAR, RAKESH; HANSRA, B S; DUBEY, NEERU; KUMAR, AMIT (The Indian Journal of Agricultural Sciences, 2022)
Terrace gardening or rooftop gardening is becoming popular in urban and peri-urban areas of metro cities worldwide including in India. Among various crops suitable for growing in terrace garden, strawberry is a popular one as being an important annual herbaceous plant with delicious fruits which can be easily grown in pots or containers including grow bags filled with different potting substrates. In the present study, different combinations of soil, organic manure (vermi-compost and FYM) and cocopeat were tested for growth, yield and physico-chemical characteristics of two strawberry cultivars (Winter Dawn and Sweet Charlie). Winter dawn was found better than Sweet Charlie for measured growth and yield parameters, and potting substrates had similar effect on both the cultivars as no interaction effect was noticed. Combination of Soil + vermi-compost + cocopeat or soil + FYM + cocopeat in equal proportion (1:1:1) was found most appropriate potting substrate for strawberry cultivation, hence suggested as a suitable growing medium for production of strawberries in terrace or rooftop gardening in peri-urban areas of Delhi/ National Capital Territory. Further investigation is needed to standardize cost-effective management agro-techniques of strawberry cultivation in terrace garden involving some other cultivars, nutrient management and environment protective structures and so on